'Time + materials: Choreographic experiments with labour and finance in The Dangerologists' Work Songs'. Issue 1 (1st July 2013) - Chow, Broderick D. V.
This article discusses the process of choreographing labour in Work Songs, a practice as research investigation in dance theatre that poses the question: how is labour as such made present and perceptible within the representational frame of the theatre? Work Songs was created between November 2011 and December 2012 by Broderick Chow and Tom Wells (The Dangerologists) and has been seen in London, Manchester, Leeds, Edinburgh and Gießen, Germany. Departing from Karl Marx's analyses of abstract and concrete labour, the article describes the economic and social context of post-Fordist production and financial capitalism to which this piece is a response. It then discusses the apparatuses of theatre and dance in terms of their 'erasure' of labour through, respectively, dramatic representation and naturalized virtuosity. It then argues that the perception of labour as such within the frame of the theatre is directly related to the interlinked dynamics of temporality and materiality – when narrative/chronological temporality is suspended, materiality is made present. This is demonstrated in Work Songs by the insertion of blockages into the smooth flow of its choreography, and the suspension of its dramatic narrative.